Livestock development initiatives - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Assisting African livestock keepers edited by CIare Oxby 1991 61pp UKL5.95 ISBN 085003 143 5 Overseas Development Institute Regent's College, Inner Circle Regent's Park, London NW1 4NS UK